Incentives for risk-taking in banking – A unified approach - Jeitschko, Thomas D.; Jeung, Shin Dong (Journal of Banking & Finance, 2005)
It is often claimed that well-capitalized banks are less inclined to increase asset risk, because the option value of deposit insurance decreases with capitalization. However, bankers, regulators and some academics challenge this view. Since the traditional view relies on studies that neglect the managerial agency problem and do not consider “higher-risk, higher-return” assets, we revisit the issue assuming that three agents – deposit insurers, shareholders, and managers – all influence banks' risk levels. We examine four distinct assumptions on the characteristics of risk–return profiles and derive conditions under which banks' risk decreases or increases with capitalization.